(untitled) (Bangladesh Journal of Botany, 2022)
Impact of anthropogenic activities on physico-chemical properties of sediment of Hokersar wetland was carried in summer, spring and autumn seasons. Sediment at Inlet site was having higher value for physicochemical parameters viz; EC (0.509 dS/m), available nitrogen (109.86 mg/kg), available potassium (89.97 mg/kg), available phosphorus (10.18 mg/kg), Ca (352.53 mg/kg) and Mg (152.44 mg/kg) except pH which was highest (7.99) at Outlet. The values of all the physico-chemical parameters of sediment were found maximum in summer season and minimum in autumn except for pH which was higher (7.81) in autumn and lower in (7.16) in summer. Highest values for Fe (23.90 mg/kg), Mn (8.54 mg/kg), Cu (3.65 mg/kg) and Zn (2.77 mg/kg) in sediment were found at Inlet site and lowest values for Fe (11.82 mg/kg), Mn (3.52 mg/kg), Cu (0.97 mg/kg) and Zn (1.14 mg/kg) at outlet site. Further, these trace elements were observed in higher concentration during summer season as compared to autumn. This all may be due to the high rate of degradation of huge quantities of waste present in the Wetland. Bangladesh J. Bot. 51(1): 83-92, 2022 (March)